2023
DOI: 10.3390/f14050923
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effects of Harvesting on the Abundance and Richness of Soil Fauna in Boreal and Temperate Forests

Abstract: The processes of matter and energy metabolism in forest ecosystems are largely dependent on the activity of the complex of invertebrates associated with litter and soil. To quantify the effect of forest harvesting on soil fauna, we used a meta-analysis to examine a database of 720 responses to harvesting collected from 52 publications from boreal and temperate forests. Overall, forest harvesting was found to decrease the abundance of soil fauna while not affecting its richness. However, the reaction of soil fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
1
2
0
Order By: Relevance
“…Secondly, they are diverse and well-studied in Khibiny Mts in terms of the species number, and thirdly, they are non-specialized mobile predators, or generalists, capable of actively migrating to disturbed areas or, conversely, avoiding them. The dominance of these taxa in clear-cuttings and burning areas at different stages of succession has been repeatedly noted in the literature sources [35,36], which can be compared with our results in the Khibiny Mts. At the same time, these taxa differ in the degree of association with the soil cover.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Secondly, they are diverse and well-studied in Khibiny Mts in terms of the species number, and thirdly, they are non-specialized mobile predators, or generalists, capable of actively migrating to disturbed areas or, conversely, avoiding them. The dominance of these taxa in clear-cuttings and burning areas at different stages of succession has been repeatedly noted in the literature sources [35,36], which can be compared with our results in the Khibiny Mts. At the same time, these taxa differ in the degree of association with the soil cover.…”
Section: Introductionsupporting
confidence: 87%
“…Therefore, even in response to the influence of one prevailing factor disrupting the soil cover, animals show a dissimilar reaction from negative or neutral to positive. This has been illustrated on examples of epigeic and endogeic fauna in neighboring northern regions: in the burn forest of the Kostomuksha Nature Reserve (Karelia Republic) [35], clear-cuttings of the Komi Republic [36], as well as in our previous studies on the fauna of clear-cuttings and burn sites in the Khibiny Mts [28,29]. Therefore, we analyzed the responses of spiders, rove beetles, and ground beetles to the clear-cutting and burning of the mountain taiga forest.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, soil invertebrates are also sensitive indicators of forest disturbances. For example, Kataja et al [16] and Kudrin et al [17] have shown that forest harvesting has a dramatic effect on soil invertebrate populations. Peguero et al [18] found that nitrogen addition resulted in a significant increase in the abundance of oribatid mites and a rapid decrease in populations of springtails, leading to changes in the soil invertebrate community in a Mediterranean forest.…”
Section: Introductionmentioning
confidence: 99%